Evolutionary lability in floral ontogeny affects pollination biology in Trimezieae - Lovo, Juliana (2021)
Premise There is little direct evidence linking floral development and pollination biology in plants. We characterize both aspects in plain and ornamented flowers of Trimezieae (Iridaceae) to investigate how changes in floral ontogeny may affect their interactions with pollinators through time. Methods We examined floral ontogeny in 11 species and documented pollination biology in five species displaying a wide range of floral morphologies. We coded and reconstructed ancestral states of flower types over the tribal phylogeny to estimate the frequency of transition between different floral types. Results All Trimezieae flowers are similar in early floral development, but ornamented flowers have additional ontogenetic steps compared with plain flowers, indicating heterochrony. Ornamented flowers have a hinge pollination mechanism (newly described here) and attract more pollinator guilds, while plain flowers offer less variety of resources for a shorter time. Although the ornamented condition is plesiomorphic in this clade, shifts to plain flowers have occurred frequently and abruptly during the past 5 million years, with some subsequent reversals. Conclusions Heterochrony has resulted in labile morphological changes during flower evolution in Trimezieae. Counterintuitively, species with plain flowers, which are endemic to the campo rupestre, are derived within the tribe and show a higher specialization than the ornamented species, with the former being visited by pollen-collecting bees only.